1669 : une diaspora méditerranéenne du xviie siècle - Eleftheria Zéi (Diasporas: Circulations, Migrations, Histoire)
The fall of Venetian Candia in 1669 and the installation of the Ottomans in the “Maritime State” of Venice provoked three forms of mobility in 17th century Mediterranean: a massive establishment of Venetian subjects from Crete in the Ionian Islands and the region of Istria, which was organized by the Venetian State in order to preserve its political and ideological domination over the Mediterranean; a wave of Cretan emigration to Venice, which ends up creating new national identities within the Venetian city; and an extreme mobility of families of “Latin” origins within the Greek Archipelago, influencing the social and economic transformations of the island societies in modern times.